Función Lineal - Rodríguez-Granados, Natalia (My University, 2017)
El video consiste en los aspectos más importantes que envuelven la función lineal. Desde la forma que posee la ecuación de la recta, hasta la importancia de algunos de sus valores como la pendiente de la recta.

The video consists of the most important aspects that involve the linear function. From the form that has the equation of the line, to the importance of some of its values as the slope of the line.
Keywords: Funciones; Puntos; Valor; Imagen